Scene adaptive structured light using error detection and correction. Issue 1 (January 2015) - Chen, Xida; Yang, Yee-Hong
Abstract In this paper, we present a new structured light 3D reconstruction method that can be applied to scenes in the presence of global illumination such as inter-reflection, subsurface scattering and severe projector defocus. The proposed method takes advantage of important properties embedded in the binary code patterns, and determines the minimum stripe width that eliminates the effects of subsurface scattering and projector defocus in the capturing stage. Moreover, errors caused by inter-reflection are detected, and corrected by an iterative approach. Our method can be applied to scenes where more than one global illumination effect appears in a scene point. The accuracy of our method is demonstrated by quantitative evaluation, and its robustness by qualitative evaluation when applying to real-world scenes with various characteristics, both of which are better than two of the currently known best methods.